2016
DOI: 10.1016/j.seizure.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Guideline conform initial monotherapy increases in patients with focal epilepsy: A population-based study on German health insurance data

Abstract: Initial monotherapy for focal epilepsy is in line with current clinical practice guidelines and mainly implemented by prescription of levetiracetam. Further evaluations should address the question of whether patients treated in line with the guidelines have a favorable outcome, compared to patients not treated in line with current guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 50 publications
4
20
1
1
Order By: Relevance
“…This study may in fact underestimate this situation as the observation started in 2007, but some of the prevalent FE patients may have received other AEDs before 2007. Thus, this study confirmed that German treatment guidelines are being strongly adhered to, with high prescription of established AEDs, and low prescription of novel AEDs [32]. …”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This study may in fact underestimate this situation as the observation started in 2007, but some of the prevalent FE patients may have received other AEDs before 2007. Thus, this study confirmed that German treatment guidelines are being strongly adhered to, with high prescription of established AEDs, and low prescription of novel AEDs [32]. …”
Section: Discussionsupporting
confidence: 82%
“…In our calendar year-based observation, the percentage of adult prevalent FE patients who did not receive any AED therapy ranged between 8.1% in 2007 to 15.4% in 2014; and it steadily increased over time. The generally lower percentage of the no-AED therapy group in comparison to the study by Ertl et al [32] can potentially be explained by our conservative sample definition which required at least one AED prescription in the whole observation period. Without knowledge about disease specifics of these patients, the pattern of the steadily increasing percentage of patients with no AED therapy may be explained by several factors: Firstly, epilepsy surgery or treatment with vagus nerve stimulation (VNS) are therapy options for drug-resistant epilepsy patients [33], [34].…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Entries contain inpatient diagnoses, outpatient diagnoses, costs, procedures, and demographics, and they are routinely inspected for outliers, data errors, and longitudinal changes. The database is continuously evaluated to ensure that it is representative of the German population by comparison to the annual publications of the German Federal Social Insurance Office (Bundesversicherungsamt [BVA]) and has been used previously for epidemiologic studies in epilepsy, SE, and multiple sclerosis . STROSA guidelines (Standardized Reporting Of Secondary data Analyses) were followed…”
Section: Methodsmentioning
confidence: 99%
“…We have chosen CBZ as it is considered the prototype of sodium channel blockers used in the treatment of people with epilepsy. LEV and LTG were selected, because they are nowadays the most widely used AEDs in the developed countries (16). Furthermore, CBZ and LTG were discussed as potential risk factors for SUDEP in previous studies (17).…”
Section: Introductionmentioning
confidence: 99%